扭杆弹簧强扭工艺及其规范制定的理论探讨 - 彭和平; 李志明 (Jixie chuandong)
The strengthening mechanism of the torsional bar spring was analized with the help of etastic and plastic theory. The technics and standardnization for strengthening were presented.